2007
DOI: 10.1007/s00417-007-0687-1
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal efficacy of voriconazole, itraconazole and amphotericin b in experimental fusarium solani keratitis

Abstract: Progression of keratitis was inhibited clinically in all treatment groups. Colony level decreased significantly in all treatment groups. As a result, itraconazole 1% and voriconazole 1% were found to be effective in Fusarium keratitis clinically and microbiologically, although their activity was not as effective as amphotericin B 0.15%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The result showed that Fusarium was susceptible to amphotericin B in 69 (97.18%) of 71 isolates but resistant to fluconazole in 91.55% of the 71 isolates. This result suggests that amphotericin B may be helpful for treatment of Fusarium keratitis 23–25 . It is a fact that not all the results of antifungal susceptibility tests in vitro are completely coincident with the therapeutic effects in vivo , because the immune defence of hosts also plays important roles in the occurrence of fungal infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that Fusarium was susceptible to amphotericin B in 69 (97.18%) of 71 isolates but resistant to fluconazole in 91.55% of the 71 isolates. This result suggests that amphotericin B may be helpful for treatment of Fusarium keratitis 23–25 . It is a fact that not all the results of antifungal susceptibility tests in vitro are completely coincident with the therapeutic effects in vivo , because the immune defence of hosts also plays important roles in the occurrence of fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that amphotericin B may be helpful for treatment of Fusarium keratitis. [23][24][25] It is a fact that not all the results of antifungal susceptibility tests in vitro are completely coincident with the therapeutic effects in vivo, because the immune defence of hosts also plays important roles in the occurrence of fungal infections. A principle about the correlation between antifungal susceptibility and therapeutic effect has been internationally accepted: if the pathogen is sensitive to an antifungal drug, treatment with this medication will be effective in 90% of patients; if resistant, therapy will be effective in 60% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, since previous reports of single case studies for AH concentrations were approximately 52-53% using oral treatment [10,11]. A comparative study of different topical antifungal treatment options was conducted by Yavas in 2007 [12]. In his animal infectious keratitis model he found effective clinical improvement in all settings through treatment with topical voriconazole.…”
Section: Discussionmentioning
confidence: 92%
“…Various reports described fungal keratitis induced experimentally in the rabbit as part of safety and efficacy testing of various antifungal agents (Lourdes Garcia et al 2002, Goldblum et al 2005, Yavas et al 2008, El -Mofty et al 2014. In contrast to other species, spontaneously occurring keratomycosis has only been reported once in a pet rabbit; fungal culture identified the pathogen as Aspergillus fumigatus (Bourguet et al 2016).…”
Section: Discussionmentioning
confidence: 99%